Problem Pengembangan Kreativitas Hakim di Tengah Intervensi Kekuasaan dan Mafia Peradilan: Bercermin dari Pemikiran Filsafat Hukum Roscoe Pound - Ahmad Syafi'i SJ (Justicia Islamica, 2009)
This study aims to examine the problems of developing the creativity of judges in dealing with the intervention of power and judicial mafias, with reference to Roscoe Pound's philosophy of law. This study uses a qualitative method with a normative legal philosophy approach, through literature analysis and relevant case studies. The results show that in Roscoe Pound's perspective, law is a tool of social engineering that requires judges to be creative in interpreting the law for substantive justice. However, the reality in Indonesia shows that the creativity of judges is often hampered by external pressures, both from political power and judicial mafia practices. This study emphasizes the need for reform of the judicial system and the protection of the independence of judges so that their strategic role as agents of legal change can develop optimally.